PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN DISTRIBUTOR BATERAI YUASA (KASUS PT. RIAU INDOTAMA ABADI PEKANBARU) - Rendi Fitriadi; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research was to determine the influence of incentives conducted in PT. Riau Indotama Abadi Pekanbaru on employee performance products distributor Yuasa battery. PT. Riau Indotama Abadi Pekanbaru is the official distributor Yuasa battery with cover marketing area Riau and Riau Islands. PT. Riau Indotama Abadi Pekanbaru has implemented incentives to employees to reward employee performance, improve the quality of employment, and meet the needs of employees. Optimal performance of employees and work in accordance with the standards of the company to realize the goals of the company. In this research, the population is employed about 31 people with a sampling technique that census. The research concludes that the incentive effect on the performance of employees at PT. Riau Indotama Abadi Pekanbaru. With evidence of regression calculation results show that t is greater than t table is 6.720 t> t table 2,045 and Sig. (0,000) <0.05.Keywords : incentives, performance, distributor